The role of digital platforms and ecosystems in the formation of the modern business model of an agrarian enterprise (Economics and region, 2024)
The article examines the influence of digital platforms and ecosystems on the formation of a modern business model of an agricultural enterprise. The indicators of the digital transformation of the agricultural sector for 2010-2022 were analyzed. Information platforms play a central role in the digital transformation of the agricultural sector, providing producers with access to large volumes of data on soil conditions, weather conditions, pests and plant diseases. The analysis of these data allows you to make informed decisions about the use of plant protection products, fertilizers and other agrochemicals, which helps to increase the yield and quality of products. Despite the potential of digital platforms for optimizing agricultural processes, their widespread implementation in Ukraine is held back by the insufficient level of development of digital infrastructure, especially in rural areas, as well as the low digital literacy of the rural population. Overcoming these limitations requires significant investment in the development of digital infrastructure and large-scale educational campaigns. The types of digital platforms used in the business models of agricultural enterprises are presented, ensuring efficiency, transparency and innovation in all aspects of production. The essence of the concept of "ecosystem" is considered, the definition of an agrarian ecosystem is given. The agrarian ecosystem is a complex network of interconnected economic entities, which includes producers of agricultural products, suppliers of resources, trading enterprises, logistics companies, as well as other interested parties. The interaction between these subjects takes place on the basis of mutual benefit and contributes to the effective functioning of the entire agricultural sector. A description of the types of ecosystems in the business model of an agrarian enterprise is given. The experience of the successful functioning of agricultural ecosystems in the Netherlands and Israel was studied. The analysis of the Ukrainian agricultural market indicates the appearance of the first signs of the formation of business ecosystems based on the interaction of large agricultural holdings with other market participants. However, existing models do not fully meet the criteria of mature ecosystems, as their functioning is limited mainly to horizontal integration processes. A SWOT analysis of the development of the digital agricultural sector of Ukraine was conducted. Identified strengths can become the basis for competitive advantage, and weaknesses - for the development of measures to eliminate them. The identification of new opportunities, such as the development of e-commerce or the use of blockchain, allows the development of innovative business models. At the same time, the identification of potential threats, for example, cyber threats or climate change, allows to develop strategies to minimize them.
Keywords: digital platforms; ecosystems; agricultural sector; business model; digital transformation; innovations